Muscle Mitohormesis Promotes Longevity via Systemic Repression of Insulin Signaling. - Owusu-Ansah, E.; Song, W.; Perrimon, N. (Cell, 2013)
Mitochondrial dysfunction is usually associated with aging. To systematically characterize the compensatory stress signaling cascades triggered in response to muscle mitochondrial perturbation, we analyzed a Drosophila model of muscle mitochondrial injury. We find that mild muscle mitochondrial distress preserves mitochondrial function, impedes the age-dependent deterioration of muscle function and architecture, and prolongs lifespan. Strikingly, this effect is mediated by at least two prolongevity compensatory signaling modules: one involving a muscle-restricted redox-dependent induction of genes that regulate the mitochondrial unfolded protein response (UPR(mt)) and another involving the transcriptional induction of the Drosophila ortholog of insulin-like growth factor-binding protein 7, which systemically antagonizes insulin signaling and facilitates mitophagy. Given that several secreted IGF-binding proteins (IGFBPs) exist in mammals, our work raises the possibility that muscle mitochondrial injury in humans may similarly result in the secretion of IGFBPs, with important ramifications for diseases associated with aberrant insulin signaling.